PENGEMBANGAN MEDIA PEMBELAJARAN SCRAMBLE WORDS PADA MATA PELAJARAN BAHASA INGGRIS KELAS IV A SD ISLAM DARUL HUDA SEMARANG - Andina Isna Ghani Saputri; Muhammad Arief Budiman; Mira Azizah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The problem was found that 57% of students found it difficult to learn English. Especially in writing and reading skills, learning media is limited. The aims of this research are 1) to know the characteristics of Scramble Words media, 2) to know the validity of Scramble Words media, 3) to know the practicality of Scramble Words media. This study uses the Research and Development (RnD) method. Data collection techniques using interviews and questionnaires. Data analysis using descriptive qualitative and descriptive quantitative. The results showed that the Scramble Words media was declared valid with a very feasible category with the results of the analysis of the media expert validation of 97.5% and the results of the analysis of material expert validation of 100%. The Scramble Words media was declared practical by obtaining a percentage of 82% in the strongly agree category, through the results of the student response questionnaire analysis. Through the results of the teacher's response questionnaire analysis, a percentage of 80% was obtained in the strongly agree category. Based on the results of this study the Scramble Words media developed was stated to be valid and practical to use in the learning process.